2019
DOI: 10.18203/2349-3291.ijcp20192033
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, profile of malnutrition and iron deficiency anemia in children with cyanotic congenital heart defects: a case control observational study in a tertiary care hospital in North India

Abstract: Background: Children with congenital heart disease (CHD) are prone to malnutrition. Children with cyanotic CHD [CCHD] are specifically affected due to chronic hypoxia and iron deficiency anemia which is overlooked by pediatrician. This can have a significant effect on the outcome of surgery. Our objective was to determine the burden and determinant of malnutrition in children with several types of cyanotic congenital heart disease (CCHD).Methods: This case-control study included 80 children with symptomatic CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…However, iron deficiency anemia is reported to be common in individuals with CCHD even in the presence of high hematocrit levels. This explanation strengthen by the study conducted in India showed that hemoglobin and hematocrit levels and RBC count were paradoxically higher in the CCHD as compared to the healthy controls [21]. Regarding the ACHD cases, the prevalence of anemia in our study was equivalent to that found in studies conducted by Mohammadi et al and Gaiha et al [16,20].…”
Section: Discussionsupporting
confidence: 85%
“…However, iron deficiency anemia is reported to be common in individuals with CCHD even in the presence of high hematocrit levels. This explanation strengthen by the study conducted in India showed that hemoglobin and hematocrit levels and RBC count were paradoxically higher in the CCHD as compared to the healthy controls [21]. Regarding the ACHD cases, the prevalence of anemia in our study was equivalent to that found in studies conducted by Mohammadi et al and Gaiha et al [16,20].…”
Section: Discussionsupporting
confidence: 85%
“…The overall prevalence was 90.4% in case group compared to 21.1% control group (Okoromah et al, 2011). The study done by Mir et al, (2019) also reported 72.5% prevalence of poor nutritional status in 29 from 40 children with CHDs compared to 22.5% prevalence of children without CHDs but had poor nutritional status (Mir et al, 2019). Similarly, in Padang and Egypt, in the study by Hermawan et al, (2015) and Hassan et al, (2015) reported higher cases of poor nutritional status in all patients with CHDs, regardless of the type of CHDs they were suffering from (Hassan et al, 2015;Hermawan et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…In their investigation, Mir AB et al, 20 found that the prevalence of malnutrition overall was 72.5% in CHD patients and 22.5% in controls. In 68.9% of instances, severe malnutrition was found to be present.…”
Section: Congenital Heart Disease and Malnutritionmentioning
confidence: 89%
“…A related study by Ossei I et al, 19 found that 47% of CHD cases had absolute iron deficit and 72.7% of cases had relative iron shortage. In their investigation, Mir AB et al, 20 found that 47.5% of the CHD population had iron deficiency anaemia (IDA). In contrast to the general population, patients with cyanotic cardiac disease had their iron deficient anaemia evaluated by Sumeet Soni et al 22 In cases of cyanotic heart disease, the mean haemoglobin was 13.39 gm/dl with a 2.38 SD.…”
Section: Prevalence Of Iron Deficiency Anaemia In Chdmentioning
confidence: 99%
See 1 more Smart Citation